Pendampingan, Edukasi Dan Sosialisasi Pencegahan Virus Corona (Covid-19) Di Desa Sidopekso Kecamatan Kraksaan Kabupaten Probolinggo - Izza, Ismatul (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
At the end of 2019 the world was shocked by the outbreak of Corona Virus Diseases or better known as COVID-19 which started from the city of Wuhan, China to various countries, including Indonesia. This virus causes all aspects of life to be affected both public health, world economy, education, social and political. The covid-19 case in Indonesia was announced by the government for the first time in February, due to the very dangerous spread of this virus, the government enforced the latest regulations such as limiting interaction with people (social distancing), working from home (Work From Home), learning online (Online) and so on. Symptoms of this virus are known as flu symptoms, starting with fever, cough, runny nose, sore throat. If a person exposed to this virus has a history of other diseases, it is very dangerous and can cause death. Many people do not understand the symptoms and dangers of the corona virus so that community mobility is still high even though transmission between humans is still high in intensity. To prevent the spread of this virus, there is a need for socialization and educating the public regarding covid-19 knowledge. With this background, Islamic University lecturer Zainul Hasan Genggong Probolinggo carried out community service activities, especially residents of Sidopekso Village in the form of Assistance, Socialization and Education on Coronavirus prevention activities which were held in May 2020.